Timing, intensity, and duration of household food insecurity are associated with early childhood development in Kenya. Issue 2 (23rd October 2017) - Milner, Erin M.; Fiorella, Kathryn J.; Mattah, Brian J.; Bukusi, Elizabeth; Fernald, Lia C.H.
Abstract: This study examines the association between 3 dimensions of food insecurity (timing, intensity, and duration) and 3 domains of child development (gross motor, communication, and personal social). Longitudinal data from 303 households ( n = 309 children) visited 9 times over 2 years were collected. Children in households experiencing severe food insecurity 3 months prior ( timing ) had significantly lower gross motor (β −0.14; 95% CI [0.27, −0.0033]; p = .045), communication (β −0.16; 95% CI [−0.30, −0.023]; p = .023), and personal social (β −0.20; 95% CI [−0.33, −0.073]; p = .002) Z‐scores, using lagged longitudinal linear models controlling for current food insecurity; these results were attenuated in full models, which included maternal education, household asset index, and child anthropometry. Children in households that experienced greater aggregate food insecurity over the past 2 years ( intensity ) had significantly lower gross motor (β −0.047; 95% CI [−0.077, −0.018]; p = .002), communication (β −0.042; 95% CI [−0.076, −0.0073]; p = .018), and personal social (β −0.042; 95% CI [−0.074, −0.010]; p = .010) Z‐scores; these results were also attenuated in full models. Children with more time exposed to food insecurity ( duration ) had significantly lower gross motor (β −0.050; 95% CI [−0.087, −0.012]; p = .010), communication (β −0.042; 95% CI [−0.086, 0.0013]; p = .057), and personal social (β −0.037; 95% CI [−0.077, 0.0039]; p = .076) Z‐scores; these results were no longer significant in full models. Our findings suggest that acute and chronic food insecurity and child development are related, but that many associations are attenuated with the inclusion of relevant covariates.